Does Mentoring Work with High-Risk Adult Probationers?: The Implementation and Outcomes of an Adult Mentoring Court - Taylor, Caitlin J. (American journal of criminal justice, 2023)
While some programs for justice system-involved adults have included mentoring as one of many different program components, a problem-solving court known as the MENTOR (Mentors Empowering Now to Overcome Recidivism) program was recently the first known program to center mentoring as the primary program component. Evaluation results suggested that program participants experienced a high quantity and quality of mentoring and case management. Using a quasi-experimental research design with a matched comparison group, outcome evaluation results revealed that the program was associated with a significant reduction in probation revocations, a marginally significant reduction in new arrests, and no significant effects on employment outcomes in the 12-month study period.